A Study on the Establishment of a Faculty of Chinese Proficient Teachers and the Development Model of Chinese Expert Thai Teachers at the Primary and Secondary level in Thailand: 泰国中小学优秀当地汉语教师团队建设与培养建议研究 - Pichai Kaewbut (Mandarinable: Journal of Chinese Studies, 2024)
The development of Chinese teachers in Thailand has been going on for a long time. At the present time, Thai Chinese teachers are the important resource persons on driving Chinese language teaching in Thailand.  The study of the establishment of a panel of Chinese language proficient teachers and the development model of Chinese language proficient teachers in the primary and secondary level in Thailand is one of the important education issues at present. The objective of this research is to study the establishment of a panel of teachers who are experts in Chinese language and the development model of Chinese language proficient teachers in the primary and secondary schools in Thailand. The data was collected from 21 training sessions from Thai Chinese teachers nationwide. Altogether 1,400 teachers participated in the training during 2020-2022. The research methods include literature analysis, observation, and focus group interview. The results of the study showed that: 1) A panel of teachers who specialize in Chinese at various levels should be established concretely. 2) The development model of Chinese proficient teachers should be categorized in development, and 3) To promote and develop in order to increase the number of expert Chinese teachers.